(untitled) (Journal of the College of Basic Education, 2022)
Experience means the set of attitudes and events experienced by the learner at a specific moment in his life, whether they are attitudes or past or current events, provided that they affect his behavior and leave traces on his personality and make him a different form from others (Taha and others, BT: 185), as well as making The learner is an active actor who knows what he is doing, how and why, and the continuity of human experience and its communication in the direction of a goal that leads the personality to sound growth in all its aspects and makes it complete and integrated. Experience (Al-Najihi, 1963: 80).